Mapping Research Conducted on Long-Term Care Facilities for Older People in Brazil: A Scoping Review - Wachholz, Patrick Alexander [UNESP]; De Oliveira, Deborah Cristina; Hinsliff-Smith, Kathryn; Devi, Reena; Fortes Villas Boas, Paulo Jose [UNESP]; Shepherd, Victoria; Jacinto, Alessandro Ferrari; Wada Watanabe, Helena Akemi; Gordon, Adam Lee; Ricci, Natalia Aquaroni (Mdpi, 2021)
This scoping review aimed to explore the characteristics, strengths, and gaps in research conducted in Brazilian long-term care facilities (LTCFs) for older adults. Electronic searches investigating the residents (>= 60 years old), their families, and the LTCF workforce in Brazil were conducted in Medline, EMBASE, LILACS, and Google Scholar, within the timescale of 1999 to 2018, limited to English, Portuguese, or Spanish. The reference lists were hand searched for additional papers. The Mixed Methods Appraisal Tool (MMAT) was used for critical appraisal of evidence. Data were reported descriptively considering the study design, using content analysis: 327 studies were included (n = 159 quantitative non-randomized, n = 82 quantitative descriptive, n = 67 qualitative, n = 11 mixed methods, n = 6 randomized controlled trials, and n = 2 translation of assessment tools). Regardless of the study design, most were conducted in a single LTCF (45.8%), in urban locations (84.3%), and in non-profit settings (38.7%). The randomized trials and descriptive studies presented the lowest methodological quality based on the MMAT. This is the first review to provide an overview of research on LTCFs for older people in Brazil. It illustrates an excess of small-scale, predominantly qualitative papers, many of which are reported in ways that do not allow the quality of the work to be assured.
Keywords: older adults; care homes; nursing homes; long-term care; older people; scoping review